Implementing Islamic Singing Activities to Instill Moral Values: A Qualitative Case Study at Al Istiqomah Kindergarten, Muara Bulian - Melly Audiah; Mahluddin; Husin (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Moral education in early childhood requires instructional approaches that are developmentally appropriate and capable of transforming moral concepts into everyday behaviors. This study aimed to explore how Islamic singing activities were implemented to instill moral values at Al Istiqomah Kindergarten, Muara Bulian, Indonesia. A qualitative descriptive case study was employed involving the school principal, one classroom teacher, and fourteen Group B children selected through purposive sampling. Data were collected through participant observation, semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed that the implementation of Islamic singing activities followed four interconnected stages: instructional planning, classroom implementation, behavioral habituation, and evaluation. Teachers integrated meaningful song lyrics with body movements, behavioral modeling, reflective discussions, and continuous reinforcement both in school and at home. These practices promoted children's active participation and contributed to observable improvements in moral behaviors, including greeting others politely, praying before and after learning activities, respecting teachers, maintaining classroom discipline, and demonstrating responsibility in daily interactions. This study contributes to the literature by highlighting the pedagogical processes through which Islamic singing activities facilitate moral value internalization rather than merely emphasizing learning outcomes. The findings provide practical guidance for teachers and school leaders in designing enjoyable, culturally relevant, and value-based learning experiences to strengthen character education in early childhood settings.